Pengembangan Media Pembelajaran Berbasis Implementasi User Interface Pada Multimedia Interaktif E-Komik - ., M. Irawan Pratama; ., Putri Ratricia; ., Adinda Fitri; ., Ali Ikhwan (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
In order to facilitate effective communication between system users and developers, the prototype was designed to provide a common perception and initial understanding of the user interface's fundamental processes. Learning media now includes a variety of multimedia types, starting with graphic images and animated videos and moving on to sound, images, and text. Particularly learning media as computerized comics.